(untitled) (ILMIY TADQIQOTLAR VA YANGI OLAM, 2026)
Military sports training of students is a direct preparation of young people for army life. Young men must come to the army physically and mentally prepared, then they will quickly adapt to army life. In sports, a young man, and then a young man, in addition to the opportunity to improve physically, also receives spiritual skills of courage, patience, overcoming oneself, which is so necessary in modern and often quite tough life. O‘smirlarni harbiy sport mashg‘ulotlariga tayyorlash bosqichda o‘quvchilarni vatan mudofaasi uchun jismonan va ruhan tayyor bo’lishlari kerak, shunda ular armiya hayotiga tez moslashadi. O‘smirlarni jismoniy sifatlaridan tashqari, zamonaviy bilimlarni olish va kelajak uchun zarur bo’lgan jasorat, sabr-toqat, o’zini yengish kabi ruhiy ko’nikmalarga ega bo’ladi.